Stereological study of collagen and elastic system in the detrusor muscle of bladders from controls and patients with infravesical obstruction - Rubinstein,Mauricio (2007)
OBJECTIVE: Compare detrusor muscle of normal and patients with infravesical obstruction, quantifying the collagen and elastic system fibers. MATERIALS AND METHODS: We studied samples taken from bladders of 10 patients whose ages ranged from 45 to 75 years (mean = 60 years), who underwent transvesical prostatectomy for treatment of BPH. Control material was composed of 10 vesical specimens, removed during autopsies performed in cadavers of accident victims, with ages between 18 and 35 years (mean = 26 years). RESULTS: The results of collagen and elastic fibers quantification (volumetric density) demonstrated the following results in percentage (mean +/- standard deviation): collagen in BPH patients = 4.89 +/- 2.64 and 2.32 +/- 1.25 in controls (p < 0.0001), elastin in BPH patients = 10.63% +/- 2.00 and 8.94% +/- 1.19 in controls (p < 0.0001). CONCLUSION: We found that the components of connective tissue, collagen and elastic system fibers are increased in the detrusor muscle of patients with infravesical obstruction, when compared to controls.